1996
DOI: 10.1111/j.1476-5381.1996.tb16735.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium entry and 5‐HT2 receptor blockade in oliguric ischaemic acute renal failure: effects of levemopamil in conscious rats

Abstract: 1 Unilateral left renal artery occlusion for 1 h in a group of 8 untreated female Sprague-Dawley rats resulted in oliguric acute renal failure (ARF) persisting for more than 6 h after reflow, i.e. after reperfusion of the kidney by removal of the arterial clamp. In a second group of 8 rats with left unilateral ARF the effects of levemopamil (L), a calcium entry blocker with 5-hydroxytryptamine2 (5-HT2) receptor antagonistic properties, were studied. Rats received L as a continuous infusion (6 mg kg-' h-') from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…which was accompanied by a rise in urinary T X excretion, suggests that enhanced glomeru lar synthesis of T X A 2 with its renal vasoconstrictor action [71,72] contributes to the reduction in G F R after BDL. In analogy, we and others found in previous studies an increased glomerular T X synthesis in experimental ure teral obstruction [73] and an initial increase in urinary T X excretion after relief of ureteral obstruction in clinical obstructive uropathy [74], Others also observed enhanced glomerular T X synthesis in experimental glycerol-in duced A R F [75] and we found increased urinary T X excretion in ischemia-induced A R F [76], Thus, T X of renal glomerular origin may be responsible for reduced G F R and RPF in these disease states as well.…”
Section: Role O F the Renal Thromboxane Systemsupporting
confidence: 60%
See 1 more Smart Citation
“…which was accompanied by a rise in urinary T X excretion, suggests that enhanced glomeru lar synthesis of T X A 2 with its renal vasoconstrictor action [71,72] contributes to the reduction in G F R after BDL. In analogy, we and others found in previous studies an increased glomerular T X synthesis in experimental ure teral obstruction [73] and an initial increase in urinary T X excretion after relief of ureteral obstruction in clinical obstructive uropathy [74], Others also observed enhanced glomerular T X synthesis in experimental glycerol-in duced A R F [75] and we found increased urinary T X excretion in ischemia-induced A R F [76], Thus, T X of renal glomerular origin may be responsible for reduced G F R and RPF in these disease states as well.…”
Section: Role O F the Renal Thromboxane Systemsupporting
confidence: 60%
“…Some increase in G F R was observed in SO rats as well, suggest ing that T X A 2 and/or PGHb contributes also to the basal renal vascular tone. We also observed recently a tempora ry beneficial effect of the T X A 2/PGH2 receptor antagonist sulotroban in the very early phase of reflow in experimen tal ischemic A R F [76] suggesting that it prevented the ini tial vasoconstriction accompanying this type of ARF.…”
Section: Role O F the Renal Thromboxane Systemmentioning
confidence: 60%
“…19 TP antagonists also protected conscious rats against ischemic ARF. 21 It has also been reported that the production of TXA 2 in ischemic-reperfusion injury might be associated with leukotriene (LT)B 4 and free radicals. 26,27 In the present study, 24 and 48 h after bilateral renal pedicle clamping for 20 min, serum creatinine levels increased in wild-type mice as well as in TP knockout mice and there were no significant differences between them.…”
Section: Discussionmentioning
confidence: 99%
“…3 Renal prostanoids have important local functions, including the regulation of renal circulatory and excretory functions. 4,5 Previous studies have shown increased renal TXB 2 release during the development of acute renal failure (ARF), 6,7,19 and some studies have reported that selective TXA-synthase inhibition, 7,8 TXA 2 receptor (TP) antagonists, 9,21 or the infusion of PGE 1 , PGE 2 , and/or PGI 2 [10][11][12][13] partially protected experimental animals from the development of this syndrome. Thus, it appears that the excessive production of TXA 2 , or an imbalance in the PGI 2 /TXA 2 ratio, serves to aggravate this condition.…”
Section: Introductionmentioning
confidence: 99%
“…It also increases the inflammatory state and provokes renal dysfunction. (Kramer et al, 1993) Rats Sulotroban can stop TXA2 dependent vasoconstriction in the early phase of AKI. (Li et al, 2009) Mice Selective EP4 receptor agonists may reduce all major manifestations of XNDI, including changes in renal morphology, and may become a new treatment strategy for hereditary nephrogenic diabetes insipidus.…”
Section: First Author Yearmentioning
confidence: 99%